SYNTACTIC RELATIONS BETWEEN THE UZBEK AND TAJIK LANGUAGES - Saitov Sukhrob Djumaydillayevich (Modern American Journals, 2025)
This article provides a comparative linguistic analysis of the syntactic levels of the Uzbek and Tajik languages. It examines the typological similarities and differences resulting from the historical interaction between the Turkic (Uzbek) and Iranian (Tajik) language families. The study highlights that while both languages share fundamental syntactic categories—such as types of syntactic connections, sentence parts, and text structure—they differ significantly in their realization models. Specifically, the paper contrasts the "modifier+head" structure predominant in Uzbek with the "head+modifier" pattern often found in Tajik. Furthermore, the morphological expression of syntactic relations (cases and postpositions in Uzbek versus prepositions in Tajik) is analyzed. The article concludes by noting that while the basic syntactic structures remain distinct, there is a strong convergence in the formation of compound and complex sentences, largely due to the borrowing of conjunctions from Tajik into Uzbek.
Keywords: Uzbek language, Tajik language, comparative syntax, linguistic typology, syntactic models, modifier-head relation, prepositions, postpositions, compound sentences, paratactic connection, hypotactic connection, linguistic interference.